Growing old in an older Brazil : implications of population ageing on growth, poverty, public finance and service delivery - Gragnolati, Michele, 1968- (Directions in development (Washington, D.C.). Human development., 2011)
Brazil is in the middle of a profound socioeconomic transformation driven by demographic change. Because of profound changes in mortality and, especially, fertility over the past four decades the population at older ages then begun to increase, a trend that will become more and more rapid as time progresses. While it took more than a century for France's population, aged 65 and above, to increase from 7 to 14 percent of the total population, the same demographic change will occur in the next two decades in Brazil (between 2011 and 2031). The elderly population will more than triple within the.